2020
DOI: 10.23917/jpis.v29i2.8501
|View full text |Cite
|
Sign up to set email alerts
|

Konseling Online Sebagai Upaya Menangani Masalah Perundungan Di Kalangan Anak Muda

Abstract: The presence of technology is changing the way people to get information and communication. In the field of counseling, information technology offers some of the latest innovations to reach out, facilitate and communicate with individuals who need help from all over the world. This qualitative research collected data through literature study by analyzing 5 research results from various academics in various countries and conducting interviews with 10 youth aged 19-23 years, and 3 counselors. The results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Asynchronous online therapy has been frequently implemented (Chester & Glass, 2006), along with synchronous online counseling carried out through chat and video conference (Bambling, King, Reid, & Wegner, 2008). In Indonesia, online counseling has been massively discussed (Ifdil & Ardi, 2013;Kirana, 2019;Prabawa, Ramli, & Fauzan, 2018;Prasetya, 2017) and many research on this topic has been reported (Bangun & Saragih, 2015;Mansyur, Badrujaman, Imawati, & Fadhillah, 2020;Prabawa et al, 2018;Prahesti & Wiyono, 2017;Setyawan, 2019;Sukoco KW & Budiman S, 2019;Sutijono & Farid, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Asynchronous online therapy has been frequently implemented (Chester & Glass, 2006), along with synchronous online counseling carried out through chat and video conference (Bambling, King, Reid, & Wegner, 2008). In Indonesia, online counseling has been massively discussed (Ifdil & Ardi, 2013;Kirana, 2019;Prabawa, Ramli, & Fauzan, 2018;Prasetya, 2017) and many research on this topic has been reported (Bangun & Saragih, 2015;Mansyur, Badrujaman, Imawati, & Fadhillah, 2020;Prabawa et al, 2018;Prahesti & Wiyono, 2017;Setyawan, 2019;Sukoco KW & Budiman S, 2019;Sutijono & Farid, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Online counselling in addition to motivating clients to rapidly seek support sooner than later, it allows counselees to talk freely and more in details about their problems in comparison with face-to-face counselling (Situmorang, 2020). Online counselling in addition to reducing the transportation cost and hassle, it can be held anywhere and interestingly, it is regarded as a great platform by young clienteles as they can freely express the problems that they are encountering without shame (Mansyur et al, 2019). Web-based intervention has become so popular and trusted by the young persons they now do not feel ashamed to discuss sensitive issues such mental health that are impacting their lives which they would not have talk about with counselor in traditional face-to-face counselling sessions (Li & Leung, 2020).…”
Section: Freedom Of Expressionmentioning
confidence: 99%
“…Therefore, without such basic knowledge, it will be extremely difficult to maximally utilize and benefit from the revolutionary and transformative power of the information, communication and technology sector even in accessing healthcare services as affirmed: online counselling is demanding and exhausting especially when it comes to reading and understanding complex text messages in order to act appropriately and without delay (Wright, 2002). The potential problems in web-counselling include counsellors' lack of ability to concisely communicate through text messages while avoiding misunderstandings (Mansyur et al, 2019). The effectiveness of web-counselling is significantly challenged because of the time it takes to compose, type and send messages (Chardon et al, 2011).…”
Section: Composing Concise and Simple Messagesmentioning
confidence: 99%
“…On the other hand, transforming face-to-face services in counseling or psychology into semi or non-face-to-face telecounseling does have many challenges [8]. The study of Mansyur, Badrujaman, Imawati, and Fadhillah also shows that although telecounseling has been carried out since 2008, various steps are needed to carry it out properly [9]. For that reason, it needs to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Various health professional organizations or professional in the counseling sector recommend using remote services for consultation or counseling activities during the pandemic of 12]. Literature review on telecounseling has been carried out using English-language literature sources [3,9]. A literature review was also conducted on other similar forms of longdistance services, namely telemental health and telepsychology with English-language sources as well [6,7].…”
Section: Introductionmentioning
confidence: 99%